PENGARUH RETURN ON ASSET(ROA), RETURN ON EQUITY(ROE) DAN EARNING PER SHARE(EPS) TERHADAP HARGA SAHAM PT. INDOFOOD CBP SUKSES MAKMUR TBK - Rizma Nazriah Hasibuan (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2020)
This study aims to determine the effect of Return On Assets (ROA), Return On Equity (ROE) and Earning Per Share (EPS) on Stock Prices at PT. Indofood CBP Sukses Makmur Tbk. This type of research is associative causal, namely research that aims to analyze the relationship between one variable with other variables. The population in this study are all financial statements at PT Indofood CBP Sukses Makmur Tbk. The sample used is financial statements at PT Indofood CBP Sukses Makmur Tbk from 2010-2017. Based on the results of the t test ROA has a significance value of 0.0220.05 and has a regression coefficient of -3054.376 which means that ROA has a negative and significant effect on the stock price at PT. Indofood CBP Sukses Makmur. ROE has a significance value of 0.0900.05, which means that partially ROE has no effect on stock prices at PT. Indofood CBP Sukses Makmur. EPS has a significance value of 0.0170.05 has a regression coefficient of 21.878 which means that partially EPS has a positive and significant influence on stock prices at PT. Indofood CBP Sukses Makmur. Based on the test results of F, ROA, ROE and EPS has a significance value of 0.0030.05 and shows the value of Fcount Ftable where 30.907 6.591 which means that simultaneously ROA, ROE and EPS have a positive and significant effect on stock prices. The value of the Determination Coefficient (R2) is 0.959. So that it can be concluded that 95.9%. stock prices are influenced by ROA, ROE, and EPS and the remainder is 4.1,% is influenced by other variables not examined in this study.